Urine washing and urinary odour profiles in relation to dominance rank status in wild male capuchin monkeys (Cebus imitator) - Alice C. Poirier; Nelle K. Kulick; Suheidy Romero Morales; Marlen Kücklich; Brigitte M. Weiß; Claudia Birkemeyer; Anja Widdig; Amanda D. Melin; Katharine M. Jack (Royal Society Open Science)
Urine plays an essential role in mammalian olfactory communication, although its potential role in primates has long been overlooked owing to focus on their visual adaptations for communication. Here, we combined behavioural and chemical data to test the role of urine in signalling male dominance in white-faced capuchins (Cebus imitator). We predicted that: (i) urine washing (i.e. depositing urine onto hands/feet and rubbing them onto substrates) is more frequently performed by alpha than subordinate males; and (ii) the chemical composition of alpha male urine is distinct from that of subordinates. We collected 457 h of focal behavioural follows and 153 urine samples from 24 males in five groups at Sector Santa Rosa, Área de Conservación Guanacaste, Costa Rica. We extracted urinary volatile compounds into thermal desorption tubes and analysed them by gas chromatography-mass spectrometry. We found that alphas urine wash more than subordinates, especially during the dry season when urinary odours can last longer and intergroup interactions are more frequent. Additionally, dominance rank predicted a modest fraction of overall sample chemical dissimilarity. Our results support the hypothesis that urine may be an olfactory signaling medium; future experimental research is needed to test the extent to which urinary odours may be cues versus evolved signals.